Symbolic upcycled medals to encourage hiker participation in Indonesia’s Mount Gede Pangrango Cleanup Program - Sanabila Fatah; Vita Jasinta Sarjono; Hanif Azhar; Ahmad Riyadi Swandhani (Universitas Muhammadiyah Malang, 2025)
Increased hiking activities in Gunung Gede Pangrango National Park have increased waste accumulation, posing environmental challenges despite ongoing cleanup efforts such as Operasi Bersih (Opsih). One key issue is the lack of recognition systems that validate hikers' contributions, especially those who voluntarily carry trash back from the mountain. This study proposes an appreciation medal made from upcycled plastic waste collected during hikes, designed to serve as both a symbolic reward and a catalyst for social change, promoting environmental responsibility, collective pride, and increased participation in volunteer cleanup programs. Using a Design Thinking approach, data were collected through observations, interviews, and questionnaires with hikers and Opsih volunteers. The 3D-printed prototype was positively received, with users valuing its symbolic significance and environmental message. These findings highlight the potential of symbolic upcycled objects to foster behavioral change and strengthen shared values around sustainability and volunteerism. Aktivitas pendakian yang meningkat di Taman Nasional Gunung Gede Pangrango menyebabkan akumulasi sampah yang semakin bertambah, menimbulkan tantangan lingkungan meskipun sudah ada upaya pembersihan seperti Operasi Bersih (Opsih). Salah satu permasalahan utama adalah kurangnya sistem pengakuan yang memvalidasi kontribusi para pendaki, terutama yang secara sukarela membawa kembali sampah dari gunung. Penelitian ini mengusulkan desain medali apresiasi yang terbuat dari limbah plastik daur ulang hasil pendakian, yang berfungsi sebagai penghargaan simbolis sekaligus katalis perubahan sosial, mendorong tanggung jawab lingkungan, kebanggaan kolektif, dan peningkatan partisipasi dalam program pembersihan sukarela. Dengan menggunakan pendekatan Design Thinking, data dikumpulkan melalui observasi, wawancara, dan kuesioner kepada pendaki dan relawan Opsih. Prototipe medali yang dicetak menggunakan teknologi 3D printing mendapat respons positif, dengan pengguna menghargai nilai simbolis dan pesan lingkungan yang terkandung. Temuan ini menyoroti potensi objek simbolis hasil daur ulang untuk mendorong perubahan perilaku dan memperkuat nilai bersama mengenai keberlanjutan dan kegiatan sukarela.